Implementation of Class Management IV SD Alkhairaat Mamboro - Rizal, Rizal; Afni, Nur; Bin. M Gagaramusu, Yusdin; Amir, Pahriadi (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
This study aims to describe the implementation of classroom management in grade IV students at Alkhairaat Mamboro Elementary School with a descriptive qualitative approach. The research was conducted to explore the dynamics of classroom management from various aspects, including the physical environment, student interaction and discipline, learning methods and media, to teacher reflection and evaluation. Data were obtained through in-depth interviews, participatory observation, and documentation, with informants consisting of principals, teachers, and students. Data analysis was conducted using the Miles and Huberman interactive model, which includes the stages of collection, reduction, presentation, and conclusion drawing and verification through triangulation and member checking. The results show that classroom management practices have reflected efforts to create a conducive learning environment, although there are still various obstacles. Flexibility in seating arrangements and awareness of cleanliness began to be implemented, but the effectiveness of the picket system and the limitations of modern learning facilities are still obstacles. Teachers' strategies in fostering discipline tend to be persuasive and educative, but not yet entirely consistent. Students favour the use of interactive methods, but the utilisation of technology is not yet optimal. In addition, reflective activities have not been structured as part of the learning quality improvement cycle. This research contributes to developing classroom management theory and practice in primary schools, particularly faith-based education. The findings emphasise the importance of a holistic approach to classroom management that includes physical aspects, behaviour, pedagogical strategies, and contextualised continuous evaluation